Implementation of CSR Program for Clean Water Well Development by PT. Chevron Pacific Indonesia to The Sakai Tribe Community - Tiara Risky; Mufid Salim; Rustono Farady Marta; Kirti Dang Longani (CHANNEL: Jurnal Komunikasi, 2022)
PT. Chevron Pacific Indonesia is one of the largest oil companies in Indonesia. Social responsibility is essential so that the company can operate smoothly and get support from the surrounding community. It is necessary to implement a good Corporate Social Responsibility (CSR) program. This study aims to determine the implementation of the Corporate Social Responsibility (CSR) program to construct clean water wells in West Minas Village, PT. Chevron Pacific Indonesia. This research method uses descriptive qualitative research and data collection methods through interviews with the field Social Performance Specialist and Government specialist and three Sakai Tribe communities in West Minas Village. The data analysis technique used in this study uses the Ground technique by Miles and Huberman. The theory used in this research is a four-stage public relations strategy planning process by Cutlip Center & Broom. The results of this study indicate that PT. Chevron Pacific Indonesia has implemented the Corporate Social Responsibility (CSR) program to construct clean water wells and has carried out all public relations strategy planning stages.